2015
DOI: 10.3945/ajcn.113.067157
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products, calcium, and prostate cancer risk: a systematic review and meta-analysis of cohort studies

Abstract: High intakes of dairy products, milk, low-fat milk, cheese, and total, dietary, and dairy calcium, but not supplemental or nondairy calcium, may increase total prostate cancer risk. The diverging results for types of dairy products and sources of calcium suggest that other components of dairy rather than fat and calcium may increase prostate cancer risk. Any additional studies should report detailed results for subtypes of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(212 citation statements)
references
References 75 publications
7
199
0
6
Order By: Relevance
“…These alternatives sources are also outlined in the Cuban document, where it is noted that 'calcium requirements for adult men are lower and can be covered through a combination of alternative sources, such as cereals, beans, egg and fish' (28) . While not explicit in the Cuban-DG, this recommendation for non-dairy calcium sources is in line with emerging research linking dairy products and prostate cancer risk (33) . While eggs are mentioned as an 'alternative source', it is important to note that, except for the shells, they are not good sources of calcium.…”
Section: Eat Your Proteinmentioning
confidence: 98%
“…These alternatives sources are also outlined in the Cuban document, where it is noted that 'calcium requirements for adult men are lower and can be covered through a combination of alternative sources, such as cereals, beans, egg and fish' (28) . While not explicit in the Cuban-DG, this recommendation for non-dairy calcium sources is in line with emerging research linking dairy products and prostate cancer risk (33) . While eggs are mentioned as an 'alternative source', it is important to note that, except for the shells, they are not good sources of calcium.…”
Section: Eat Your Proteinmentioning
confidence: 98%
“…Whereas, potential adverse outcomes associated with excess intake of vitamin D may include hypercalcemia, hypercalciuria, falls and fractures, PCa and all-cause mortality [248] . A recent systematic review and metaanalysis of prospective studies reported that although increased dairy or calcium intake was associated with an increased risk of PCa, no association was observed with supplemental or non-dairy calcium, which suggest that other components of dairy rather than fat and calcium may increase PCa risk [252] . In line with these mixed findings, supplementation at doses < 1,500 mg/d have been shown to either have no influence on PCa progression [253] , reduce PCa risk [254] or decrease PSA velocity [255] .…”
Section: The Role Of Nutritional Supplementation On Muscle Fat and Pmentioning
confidence: 99%
“…bone health and nutritional quality), to low for items associated with less known and/or controversial associations (e.g. cancer development, [43][44][45][46][47] diabetes mellitus 48 and environmental concerns 49,50 ). The positive attitudes should be strengthened, whereas empowerment regarding interpretation of complex matters should be undertaken.…”
Section: Milkmentioning
confidence: 99%